Is the education on digital libraries adequate - Liu, Yan Quan (New Library World, 2004)
This study investigates the state of education for digital libraries. For this study, a Web survey was conducted of syllabi of courses on the subject of digital libraries (DL). Similarities and differences on such subjects as teaching emphases, course outlines, textbooks and assignments were compared. The majority of classes now contain a “hands-on” element, a practical component of the course that requires that the students interact with digital libraries. Not all of the course contents are up-to-date in the field of library and information technology. While the quality of DL education seems to have advanced at those schools and institutions that offer classes with “hands-on” requirements, the educational approach at many of the “hands-off” universities seems somewhat technophobic and overly dependent on outdated pedagogical methods. Those students who have received practical experience with digital libraries, like those provided in the “hands-on” courses, appear to be best served for future practice in the field of librarianship. © 2004, Emerald Group Publishing Limited
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-352-432-311-492 tex.type: [object Object]
Keywords: Digital libraries; Europe; Libararies; Library facilities; North America; Surveys; dept.ils